الأفعال السردية بين الاستطرادات والاختزالات -قراءة في رواية حوبة ورحلة البحث عن المهدي المنتظر- لعز الدين جلاوجي - عاشـور, شفيـقة (قــــــراءات; No 07-06 (2014): (مجلة قراءات( نوفمبر, 2019)
يتناول المقال بالدراسة والتحليل اختزالات الأفعال السردية واستطراداتها  في رواية "حوبة"؛ ونحن لا ندّعي الإلمام بكامل التقنيات والميكانيزمات  التي استعان بها المبدع الجزائري" عزالدين جلاوجي" في رسم خيوطه الروائية، فحسبنا فقط أن نتناول الآليات المهمة التي استخدمها لنسج وبناء نصه السردي، فاستعان بالاختزالات في الحالات التي يريد فيها الوصول إلى مغزاه في أقصر وقت ممكن، والاستطرادات في الحالات التي يسعى فيها للتنفيس والاستراحة. Summary The article studies and analyses the abbreviations and the redundancy of the narrative acts in the novel hobba; we do not claim full knowledye of the techniques and the mechanisms that are used by the Algerian novelist  and creator " Azzeddine Djlauodji" in weaving the strings of his novel. We have only to deal with the important mechanisms that the author used to weave his narrative tesct, the author has used the abbreviations where he wants to reach significance in the shortest possible time and he has used redundancy in cases where he endeavors to vent and break.